Tracking of tissue movement using distance-weighted log ratio similarity matching algorithm - Rohana, Abdul Karim; Mohd Marzuki, Mustafa; Mohd Asyraf, Zulkifley (UTeM, 2018)
Nowadays, the growth of health care quality awareness lead to the advancement of the medical technologies, especially for surgery technologies. In the field of computer vision, tracking of the tissues and internal organs (TDOD) movements have been beneficial to many surgical technologies such as computer-assisted surgery and minimally invasive surgery. TDOD tracking poses a challenging task due to the nature characteristic of TDOD which mainly has a homogenous surface and texture. We proposed a feature point tracking algorithm based on hypothesis testing t-test as a novel technique for TDOD tracking. This algorithm is based on the distance weighted log ratio t-test similarity measurement. The algorithm has been tested and showed it can perform better compared with existing methods in all the test datasets.